The relationship between psychological and physiological stress perceived by elite shooters - Park, S.-H.; Jeon, J.-Y.; Lim, S.-T. (Korean Journal of Sport Science, 2020)
Purpose: The purpose of this study was to provide useful information on the improvement of performance by measured the psychological-physiological stresses experienced by elite shooters during a competition.